Clinical insights into dermatofibrosarcoma protuberans - Arias, Francisco J. C.; Campa, Kassandra J. E.; Campa, Alondra Y. E.; Estrada, Jorge L. G.; Meza, Guillermo C. G. (International Journal of Research in Medical Sciences, 2023)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive cutaneous soft tissue sarcoma, it is the second most common skin sarcoma after Kaposi’s sarcoma. The cause of DFSP remains unknown. The case of a 54-year-old female patient with a diagnosis of Dermatofibrosarcoma protuberans is presented, displaying a typical clinical presentation. It is characterized by an initial lesion in the form of a reddish spot on the anterior region of the chest, which showed slow growth until the development of a multinodular and irregular lesion with multiple recurrences. The lesion is resected, confined to the superficial layers of the skin, with 3 cm margins, confirming the histopathological diagnosis of dermatofibrosarcoma protuberans with clear margins. DFSP is an uncommon cutaneous sarcoma that is typically low- to intermediate-grade, and while it has a limited likelihood of metastasis, it exhibits a notable tendency for local recurrence. The risk of recurrence is closely linked to the extent of surgical resection.